Examining Africentric Cultural Values, Ethnic Identity, and Substance Use Abstinence in Low-Income, Early Adolescent, African American Girls. (January 2018) - Sanchez, Delida; Hamilton, Emma R.; Gilbert, Dorie J.; Vandewater, Elizabeth A.
An examination of cultural protective factors that foster substance use abstinence among low-income, early adolescent, African American girls may be helpful in understanding how to promote resilience and reduce negative health outcomes. This study examined the relations between Africentric cultural values, ethnic identity, and substance use abstinence among 196 low-income African American early adolescent girls (age 11-14 years). Results of logistic regressions revealed that Africentric values were negatively linked to cigarette and alcohol abstinence. Results also showed a significant positive interaction between Africentric cultural values and ethnic identity exploration that contributed to increased cigarette and alcohol abstinence. Implications for research and practice with African American early adolescent girls are discussed.